Induction of lysogenic bacteriophages of Shiga toxin-producing Escherichia coli by antimicrobial growth promoters used in food- producing animals in South Africa - Karama, Musafiri (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2023.